Effect of lime on some physical parameters of a natural expansive clay from Algeria. Issue 1 (2nd January 2017) - Bourokba Mrabent, Souad Amel; Hachichi, Abdelkader; Souli, Hanène; Taibi, Said; Fleureau, Jean-Marie
Abstract : Over the last three decades, highly plastic soils have been one of the major sources of problems in roads, railways and buildings in Algeria. In these cases, soil treatment is essential to improve the engineering properties of these materials. The aim of this article was to study the effect of added lime on the physical properties of soil. Experiments were performed on a local natural clayey soil in order to investigate the influence of lime on consistency limits, total specific surface, compaction characteristics, swelling potential and swelling pressure. In addition, mercury intrusion porosimetry tests were carried out to determine the pore size distribution of the untreated and treated samples. The results show that the liquid limit decreases, the plastic limit increases and the total specific surface area decreases with the percentage of added lime. Compaction characteristics are affected by the addition of lime, the optimum water content increasing and the maximum dry unit weight decreasing in the presence of a high amount of lime. This stabilisation method leads to significant reductions in the swelling of the studied soil, exceeding 60%. The treatment with a high percentage of lime significantly reduces the average pore diameter of the treated clay.